2019
DOI: 10.1039/c9ra06823f
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative differences between common control banding tools for nanomaterials in workplaces

Abstract: A number of control banding (CB) tools have been developed specifically for managing the risk of exposure to engineered nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The CB tool of Stoffenmanager-Nano can be used to effectively assess the risk of nanoparticles in the workplace. 23,34 In this study, the Stoffenmanager-Nano model shows that the blast furnace workers exposed to high levels of ultrafine particles were at high risk level, suggesting that the existing exposure control measures were insufficient. According to the National Institute for Occupational Safety and Health regulation, 35 the most desirable alternative for mitigating risks is to employ the following additional measures: (i) the exhaust speed of LEV for dust removal at the blast furnace needs to be increased, including the redesign of the hood for total enclosure; (ii) the preventative maintenance schedule for ensuring the effectiveness of engineering control measures should be established; sensitive indicators for ultrafine particles need to be developed in occupational health examination; and (iii) regular inspection should be conducted to ensure workers are properly wearing the PPE.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The CB tool of Stoffenmanager-Nano can be used to effectively assess the risk of nanoparticles in the workplace. 23,34 In this study, the Stoffenmanager-Nano model shows that the blast furnace workers exposed to high levels of ultrafine particles were at high risk level, suggesting that the existing exposure control measures were insufficient. According to the National Institute for Occupational Safety and Health regulation, 35 the most desirable alternative for mitigating risks is to employ the following additional measures: (i) the exhaust speed of LEV for dust removal at the blast furnace needs to be increased, including the redesign of the hood for total enclosure; (ii) the preventative maintenance schedule for ensuring the effectiveness of engineering control measures should be established; sensitive indicators for ultrafine particles need to be developed in occupational health examination; and (iii) regular inspection should be conducted to ensure workers are properly wearing the PPE.…”
Section: Discussionmentioning
confidence: 70%
“… 22 Comparative studies between different CB tools showed the Stoffenmanager‐Nano model had a comprehensive advantage. 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, the Stoffenmanager-Nano and Nanotool, which are appropriate for nanoparticles and have a comprehensive advantage in risk assessment 22 , 23 , were selected for this study. The CB methodology for CB tools is briefly described as follows: The Stoffenmanager-Nano ( http://nano.stoffenmanager.nl/ ), which follows a stepwise binary decision tree and provides three risk levels 26 , 27 , was developed by the Organization for Applied Scientific Research based in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…The control banding (CB) tools evaluate the hazard risk and exposure risk by setting different parameters, and then obtain risk levels and protective measures based on a tiered approach. The CB tools, which offer simplified guidance for managing the risks from exposure to substances without toxicological and/or detailed exposure information, are applicable methods and have been used for risk assessments of different ultrafine particle exposure levels in various work environments 20 23 . In previous studies, CB tools were compared qualitatively and quantitatively under experimental or real nanomaterial exposure scenarios, and different tools to estimate hazard and exposure bands can result in different outcomes and preventive recommendations 22 25 .…”
Section: Introductionmentioning
confidence: 99%